Method to extract intact and pure RNA from mycobacteria - Akhtar, Shamim; Sarkar, Sampa; Mishra, Abhishek; Sarkar, Dhiman (Analytical Biochemistry, 2011)
We describe a high-yielding, simple, and aerosol-free protocol for the isolation of RNA from mycobacteria that does not require sophisticated instruments. The method yielded 50 mu g of RNA from 10(7) cells, 50 times more than a recently reported method. Our method can extract total RNA from aerobically grown bacteria and from in vitro hypoxia-induced dormant bacilli and mycobacteria residing within infected macrophages. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Dormant; Hypoxia; Mycobacteria; RNA isolation; Spheroplast; Trizol

Novel screening method based on menadione mediated rapid reduction of tetrazolium salt for testing of anti-mycobacterial agents - Singh, Upasana; Akhtar, Shamim; Mishra, Abhishek; Sarkar, Dhiman (Journal of Microbiological Methods, 2011)
A microplate-based rapid, inexpensive and robust technique is developed by using tetrazolium salt 2, 3-bis [2-methyloxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide (XTT) and menadione to determine the viability of Mycobacterium tuberculosis, Mycobacterium bovis BCG and Mycobacterium smegmatis bacilli in microplate format. In general, XTT reduction is an extremely slow process which takes almost 24 h to produce a detectable signal. Menadione could drastically induce this reduction to an almost equal extent within a few minutes in a dose dependent manner. The reduction of XTT is directly proportional to the cell concentration in the presence of menadione. The standardized protocol used 200 mu M of XTT and 60 mu M of menadione in 250 mu l of cell suspension grown either in aerobic or anaerobic conditions. The cell suspension of M. bovis BCG and M. tuberculosis were incubated for 40 min before reading the optical density at 470 nm whereas M. smegmatis was incubated for 20 min. Calculated Signal/Noise (S/N) ratios obtained by applying this protocol were 5.4, 6.4 and 9.4 using M. bovis BCG. M. tuberculosis and M. smegmatis respectively. The calculated Z' factors were > 0.8 for all mycobacterium bacilli indicating the robustness of the XTT Reduction Menadione Assay (XRMA) for rapid screening of inhibitors. The assay protocol was validated by applying 10 standard anti-tubercular agents on M. tuberculosis, M. bovis BCG and M. smegmatis. The Minimum Inhibitory Concentration (MIC) values were found to be similar to reported values from Colony Forming Unit (CFU) and REMA (resazurin microplate assay) assays. Altogether. XRMA is providing a novel anti-tubercular screening protocol which could be useful in high throughput screening programs against different physiological stages of the bacilli. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Menadione; Mycobacterium tuberculosis; Tetrazolium salt; XRMA

Hydroxyl radical generation in mycobacterial cell is an essential process for breaking dormancy and maintenance of active state by stepwise metabolic shift - Mishra, Abhishek (Free Radical Biology and Medicine, 2013)

Advanced cell-based high-throughput screening assays targeting active and latent Mycobacterium tuberculosis - Shurpali, Ketaki Dilip; Singh, Upasana; Sarkar, Shamim Akhtar Sampa; Mishra, Abhishek; Kulkarni, Roshan; Joshi, Swati P.; Sarkar, Dhiman (Journal of Biotechnology, 2014)

Qualitative and quantitative proteomic analysis of vitamin C induced changes in mycobacterium smegmatis - Mishra, Abhishek; Sarkar, Dhiman (Frontiers in Microbiology, 2015)
Vitamin C is a critical dietary nutrient in human which has a wide range of regulatory effects on gene expression and physiology of Mycobacterium tuberculosis that leads to a dormant drug-tolerant phenotype. In the presence of iron, vitamin C shows a high bactericidal activity even in the drug resistant phenotype of M. tuberculosis. The regulatory mechanisms underlying vitamin C induced adaptations are largely unknown due to lack of functional genomics data in this field. In this study, we attempt to characterize the direct effect of vitamin C treatment on the physiology of actively growing Mycobacterium smegmatis. The study chose M. smegmatis as it is a fast-growing bacterium and a non-pathogenic model system which shares many physiological features with the pathogenic M. tuberculosis including dormancy and its regulation. The proteomic adaptation of M. smegmatis on vitamin C treatment demonstrates the important changes in cellular and metabolic process such as reversal of tricarboxylic acid cycle, decrease in ATP synthesis, decrease in iron acquisition and storage, and induction of dormancy regulators WhiB3, PhoP, and Lsr2.
Keywords: dormancy; Mycobacterium smegmatis; proteomics; tuberculosis; vitamin C

Synthesis of ecofriendly fluorescent carbon dots and their biomedical and environmental applications - Joshi, Preeti Nigam; Mathias, Anjelica; Mishra, Abhishek (Materials Technology, 2018)
Green Synthesis of nanoparticles is an emerging field with enormous advantages over conventional synthesis methods. Herein we have reported a green method for the preparation of water soluble polydisperse carbon dots (c-dots) from Cocos nucifera frond pinnae by a modified version of the `single step hydrothermal carbonization'. C-dots having blue emission were obtained with this method and we further evaluated the effect of metal ions interactions on c-dots, as a sharp decrease in photoluminescence was observed. The synthesized c-dots were found bioactive against B.subtilis, M. smegmatis and S. aureus as determined by the well diffusion assay. We also explored nanotheranostic applications of c-dots as biosensor matrix in DNA hybridization sensor for pancreatic cancer and in bioimaging of cancer cells. This study demonstrated that c-dots can be explored for numerous biomedical and environmental applications in a variety of fields owing to the cost effective synthesis, biocompatibility and excellent physico-chemical properties.
Keywords: Carbon dots; differential pulse voltammetry; DNA hybridization sensor; green synthesis; Pancreatic Cancer